Technology drivers : engine for growth : proceedings of the 6th Nirma University International Conference on Engineering (NUiCONE 2017), November 23-25, 2017, Ahmedabad, India /: engine for growth : proceedings of the 6th Nirma University International Conference on Engineering (NUiCONE 2017), November 23-25, 2017, Ahmedabad, India. (2018) - Unknown
No abstract available